Modification of poly(vinyl chloride) with new aromatic thiol compounds. Synthesis and characterization - Navarro, Rodrigo (2008)
Different thiol compounds were tested for the synthesis of poly(vinyl chloride) (PVC) with halogen groups and the course of the modification reactions followed under different conditions by NMR spectroscopy and elemental analysis. It is shown that PVC can be modified without side reactions using 4-fluorothiophenol, 4-chlorothiophenol, 4-bromothiophenol, 3,4-di-fluorothiophenol, penta-fluorothiophenol and pentachlorothiophenol. The reactivities and final degrees of modification of the different nucleophiles are compared showing that, when the thiolate salt is preformed, the bromine derivative reacts quicker and higher degrees of modification are reached than with its smaller homologues. On the other hand, using the thiol compounds in combination with potassium carbonate this order is inverted and highest degrees of modification are achieved with 4-fluorothiophenol. Glass transition temperatures and thermal stabilities of the new compounds are compared.